2002
DOI: 10.1142/s0217732302007272
|View full text |Cite
|
Sign up to set email alerts
|

Radiation From a Charge Circulating Inside a Waveguide With Dielectric Filling

Abstract: The emitted power of the radiation from a charged particle moving uniformly on a circle inside a cylindrical waveguide is considered. The expressions for the energy flux of the radiation passing through the waveguide cross-section are derived for both TE and TM waves. The results of the numerical evaluation are presented for the number of emitted quanta depending on the waveguide radius, the radius of the charge rotation orbit and dielectric permittivity of the filling medium. These results are compared with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 4 publications
3
16
0
Order By: Relevance
“…where the coefficients D (p) m are defined by formulae (17). The case ω 0 = 0 for a fixed ρ 0 corresponds to a charge moving with constant velocity v on a straight line ρ = ρ 0 parallel to the cylinder axis.…”
Section: Spectral-angular Distribution Of the Radiation Intensitymentioning
confidence: 99%
See 2 more Smart Citations
“…where the coefficients D (p) m are defined by formulae (17). The case ω 0 = 0 for a fixed ρ 0 corresponds to a charge moving with constant velocity v on a straight line ρ = ρ 0 parallel to the cylinder axis.…”
Section: Spectral-angular Distribution Of the Radiation Intensitymentioning
confidence: 99%
“…This term dominates the contribution coming from other terms in Eqs. (15), (17) by the factor γ 1 . It can be seen that the radiation intensity as a function on ϑ has sharp peaks at the points ϑ = ϑ l corresponding to the zeros of the Bessel function J m (λ 0 ρ 1 ), i.e.…”
Section: Helical Undulatormentioning
confidence: 99%
See 1 more Smart Citation
“…where n ρ is the unit vector of the cylindrical surface. By making use of formulas (12), (15), and (16), we obtain…”
Section: Spectral-angular Distribution Of the Radiation Intensitymentioning
confidence: 99%
“…Wellknown examples are Cherenkov, transition, and diffraction radiations. In a series of papers [3][4][5][6][7][8][9][10][11] the synchrotron radiation is considered from a charge rotating around a dielectric ball/cylinder enclosed by a homogeneous medium. It has been shown that the superposition between the synchrotron and Cherenkov radiations leads to interesting effects: under the Cherenkov condition for the material of the ball/cylinder and the particle velocity, strong narrow peaks appear in the radiation intensity.…”
Section: Introductionmentioning
confidence: 99%